Efektivitas Pembelajaran Berbasis STEAM (Science, Technology, Engineering, Art, and Mathematics) untuk Meningkatkan Hasil Belajar IPAS di Kelas V Siswa SD Negeri Srondol Wetan 06 - Khoirrunnisa, Tsinta; Isdaryanti, Barokah (LPPM Institut Pendidikan Nusantara Global, 2024)
Based learning to improve IPAS learning outcomes in class V students of Srondol Wetan 06 State Elementary School. this is quantitative research with research design Quasi-experimental research design with the form of nonequivalent control group design. The sample in this study were all students of grade V of Srondol Wetan 06 State Elementary School totaling 58 students. students. Data analysis in this study used normality test, homogeneity test, t-test, and N-game test.homogeneity test, t-test, and N-gain test. The results of data analysis in this study namely the results of the t-test (Independent Sample Test) data obtained Sig (2- tailed)< α (0.001 < α), thus STEAM-based learning is effective to improve student learning outcomes.to improve student learning outcomes. And reinforced by the results of the experimental class N-gain test obtained an average N-gain value of 0.65.average N-gain of 0.65 with a medium category which is interpreted as quite effective, so it can be concluded that STEAM-based learning is effective.effective, it can be concluded that STEAM-based learning is quite effective to improve the learning outcomes of IPAS class v.